PROSES MENCAPAI IKHLAS PADA IBU RUMAH TANGGA YANG MENGALAMI PENOLAKAN DI LINGKUNGAN KELUARGA SUAMI - Susanti, Oktavia Dwi; Alifa Asyafila Rahmadani (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to examine the process of attaining ikhlas (sincere acceptance) among housewives who experience rejection from their husband’s family and its influence on their emotional condition and mental health. Rejection within family relationships can create psychological distress, including feelings of sadness, disappointment, being unappreciated, and social exclusion, which may affect self-perception, marital relationships, and overall well-being. This research used a qualitative approach with a phenomenological method to understand participants’ lived experiences in depth. Participants were selected through purposive sampling and consisted of housewives who had experienced rejection from their husband’s family. Data were collected through in-depth interviews and analyzed using thematic analysis. The findings show that attaining ikhlas occurs gradually through several stages, including experiencing rejection, the emergence of negative emotions, efforts to find meaning in these experiences, and strengthening spiritual practices such as prayer (du’a), remembrance (dhikr), and trust in Allah (tawakkul). Ikhlas is understood as an active process of accepting reality, managing emotions more adaptively, and releasing expectations of acceptance. Participants who approached ikhlas reported greater inner calm and emotional stability, although not all were able to achieve full acceptance due to lingering emotional wounds and ongoing family conflict.